Predictive Performance of Serum S100B Versus LDH in Melanoma Patients: A Systematic Review and Meta-Analysis - Janka, Eszter Anna; Várvölgyi, Tünde; Sipos, Zoltán; Soós, Alexandra; Hegyi, Péter; Kiss, Szabolcs; Dembrovszky, Fanni; Csupor, Dezső; Kéringer, Patrik; Pécsi, Dániel; Solymár, Margit; Emri, Gabriella (Frontiers in Oncology, 2021)
Background: Currently, no consensus on the use of blood tests for monitoring disease recurrence in patients with resected melanoma exists. The only meta-analysis conducted in 2008 found that elevated serum S100B levels were associated with significantly worse survival in melanoma patients. Serum LDH is an established prognostic factor in patients with advanced melanoma. Objective: To compare the discriminative and prognostic ability of serum S100B with that of serum LDH in patients with melanoma. Methods: This systematic review and meta-analysis were reported in accordance with the PRISMA Statement. The study protocol was registered in the International Prospective Register of Systematic Reviews (PROSPERO; CRD42019137138). Results: A quantitative analysis of data from 6 eligible studies included 1033 patients with cutaneous melanoma. The discriminative ability of serum S100B at identifying disease relapse (pooled Area Under the ROC (AUROC) 78.64 [95% CI 70.28; 87.01]) was significantly greater than the discriminative ability of serum LDH (AUROC 64.41 [95% CI 56.05; 7278]) (p=0.013). Ten eligible studies with 1987 patients were included in the risk of death analysis. The prognostic performance of serum S100B (pooled estimate of adjusted hazard ratio (HR) 1.78 [95% CI 1.38; 2.29]) was independent but not superior to that of serum LDH (HR 1.60 [95% CI 1.36; 2.29]). Limitations: A relatively small number of articles were eligible and there was considerable heterogeneity across the included studies. Conclusions: Serum biomarkers may provide relevant information on melanoma patient status and should be further researched. Serum S100B is a valid marker for diagnosis of melanoma recurrence.